2008
DOI: 10.1123/pes.20.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences in Activity, Fitness, and BMI in Female Eighth Graders Categorized by Sports Participation Status

Abstract: The purpose of this study was to identify racial differences in physical activity (PA), fitness, and BMI in female 8th-grade sports participants and nonparticipants. Girls from 31 South Carolina middle schools (N = 1,903, 48% White; mean age = 13.6 ± 0.63) reported PA and previous year sports-team participation, completed a submaximal fitness test, and had height and weight measured. Sports team participation was positively associated with PA and negatively associated with television viewing and BMI, in a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
5
25
0
Order By: Relevance
“…Our finding supports previous research demonstrating sports were related to a substantially lower risk of both overweight/obesity and obesity. [1][2][3][4][5][6] Because of adjustments, our estimate may more accurately reflect the influence of sport team participation compared with cross-sectional studies of US adolescents, which revealed larger effect sizes. 6 Our finding that active commuting to school was inversely related to obesity differs from previous studies that did not support this relationship.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our finding supports previous research demonstrating sports were related to a substantially lower risk of both overweight/obesity and obesity. [1][2][3][4][5][6] Because of adjustments, our estimate may more accurately reflect the influence of sport team participation compared with cross-sectional studies of US adolescents, which revealed larger effect sizes. 6 Our finding that active commuting to school was inversely related to obesity differs from previous studies that did not support this relationship.…”
Section: Discussionmentioning
confidence: 91%
“…Sports participation has been inversely related to overweight/ obesity [1][2][3][4][5][6] with some variation by sport. 5,7 Elkins et al 7 found that football was associated with an increased risk of overweight/obesity, whereas basketball, track, and cheerleading were associated with a decreased risk of overweight/obesity.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] In young girls, sports team participation was associated with increased physical activity and reduced television viewing and body mass index (BMI) in a dose-response fashion. 6 In this same pattern, fifth grade children who participated in recreational sport programmes throughout the year demonstrated increased fitness performance over their peers who did not participate in any sport or only participated in one sport. 7 In fourth and fifth grade children, the addition of an after-school soccer programme effectively decreased BMI z-scores at 3 and 6 months and influenced increases in daily, moderate and vigorous physical activity at 3 months.…”
Section: Introductionmentioning
confidence: 86%
“…50, 74 In young girls, sports team participation was associated with increased physical activity and reduced television viewing and BMI in a dose-response fashion. 57 In this same pattern, fifth grade children who participated in recreational sport programs throughout the year (fall, winter, and spring) demonstrated a greater level of increased fitness performance than their peers who did not participate in any sport or who only participated in one sport. 27 …”
Section: Integrative Educationmentioning
confidence: 87%